Organoids for Advanced Therapeutics and Disease Models. Issue 1 (30th September 2018) - Kim, Suran; Cho, Ann‐Na; Min, Sungjin; Kim, Sooyeon; Cho, Seung‐Woo
Abstract: Organoid culture is a fast‐emerging technology in the biological and biomedical research fields, garnering interest due to its unique features of self‐organization from diverse types of stem cells and close resemblance to organs in the human body. This innovative in vitro model system presents the possibility of significant advances in the understanding of human development and disease mechanisms as well as in the discovery of novel diagnostics and therapeutics. Here, the authors review several types of tissue‐specific organoids and discuss the most recent studies on the biomedical application of organoids. Finally, the challenges and prospects of organoids as an in vitro model system are laid out. Abstract : An advanced technology for generating 3D mini‐organs derived from tissue‐specific stem cells and pluripotent stem cells, called organoids, is newly emerging. This review summarizes the current stem cell–based brain, cardiac, liver, gastric, and intestinal organoid technologies and discusses the potential of organoids as valuable tools for disease modeling, drug screening, and regenerative medicine.